Modeling volatility of the KLCI daily returns / Siti Meriam Zahid ... [et al.] - Zahid, Siti Meriam; Zainol, Mohammad Said; Mohamed Sani, Ibrahim; Zaharim, Azami (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
Volatility is a central concept in financial engineering. It may be simply defined as the standard deviation of return values. A frequent modeling assumption is that volatility is constant. Unfortunately in many financial time series volatility appears to be anything but constant. This paper reports the results of an effort in modeling stock market volatility as a Generalized Autoregressive Conditional Heteroscedastic (GARCH) process.